Ester‐linked ubiquitination by HOIL‐1 controls immune signalling by shaping the linear ubiquitin landscape. (28th July 2021) - Pruneda, Jonathan N.; Damgaard, Rune Busk
Abstract : Ester‐linked ubiquitination of serine or threonine residues – or even lipids – has emerged as a new regulatory earmark in cell signalling. Petrova et al . (2021) now reveal that ubiquitin esterification by the atypical ubiquitin ligase HOIL‐1, a component of the LUBAC complex, is critical for proper formation of linear ubiquitin chains and control of immune signalling in T cells and macrophages. Surprisingly, ester‐linked ubiquitination can either promote or inhibit linear ubiquitin conjugation and cytokine production depending on the receptor and immune cell engaged. Comment on: https://doi.org/10.1111/febs.15896 . Abstract : Ester‐linked ubiquitination of serines or threonines has emerged as a regulatory earmark in cell signalling. Petrova et al . now reveal that ubiquitin esterification by the ubiquitin ligase HOIL‐1, a component of the LUBAC complex, is critical for proper formation of linear ubiquitin chains and control of immune signalling. Surprisingly, ester‐linked ubiquitination can either promote or inhibit linear ubiquitin conjugation and cytokine production depending on the receptor and immune cell engaged. Commentary on "HOIL‐1‐catalysed, esterlinked ubiquitylation restricts IL‐18 signaling in cytotoxic T cells but promotes TLR signalling in macrophages" by Petrova, et al. (FJ‐20‐1384.R1). Comment on: https://doi.org/10.1111/febs.15896 .